DIRECTIONS FOR INCREASING THE FINANCIAL OPPORTUNITIES OF PROFESSIONAL EDUCATIONAL INSTITUTIONS - Begaliev Azam Olimnazarovich (Research Parks Publishers, 2023)
This article describes the formation of financial resources of professional educational institutions, the regulatory basis of obtaining additional financial resources and the directions of their use. At the same time, problems in increasing the financial capabilities of professional educational institutions, proposals aimed at their elimination and prevention of future occurrences were noted.